Tecnologia na educação: audiovisual como ferramenta de ensino - SAMPAIO, Raicley Contadini (Instituto Federal do Amapá, 2021)
This paper aims to investigate teaching methodologies and the use of technological tools that may be able to assist in this process, in order to offer a diversified way of encouraging students from the public school system in the act of reading and writing. the proposal to use audiovisual as a teaching and learning tool, the study used resources present in the students' daily life, the cell phone, as well as external resources such as professional cameras and audio recording devices, in order to provide the creation of audiovisual material of quality, the application of this work assists teachers of Portuguese language and literature, discipline where the act of reading and writing is essential, and that the great lack of incentives to motivate students, the production of audiovisual content then brings an innovative methodology, where the students will receive technical knowledge about the area and then merge with the met Portuguese language, students work their creativity in the creation and scripts that address social or literary themes, thus practicing their reading in research related to their theme and writing in the writing of the script, given that technology attracts the student, relate It with education provides a more attractive and innovative teaching practice, motivating the student to seek knowledge and develop their enhancement of intellectual wealth.